Pancreas preserving distal duodenectomy: a versatile operation for a range of infra-papillary pathologies - Mitchell, W. Kyle; Thomas, Pradeep F.; Zaitoun, Abed M.; Brooks, Adam J.; Lobo, Dileep N. (Baishideng Publishing Group, 2017)
AIM